(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2022)
The aim of the article is to present the transport problems of Warsaw, Bratyslava and Budapest and examples of their solutions. This analysis was aimed at showing how important an element of city management is the efficient functioning of public transport. The publication presents the issues related to the city, city logistics and transport problems, along with examples of solutions in the analyzed capitals. The research methods used in the article are the analysis of book sources and internet resources.